ANALISIS PENERAPAN TAX REVIEW ATAS PAJAK PENGHASILAN BADAN DAN WITHHOLDING TAX PADA HOTEL X - Andini A. P., Luh Gita; Sumadi, Kadek (E-Jurnal Akuntansi, 2014)
Tax review is a review of the activities of the entire transaction the company to calculate the amount of tax payable and predict the potential taxes that may arise based on tax regulations. This study is investigating the application of corporate income tax review and tax withholding as the basis for evaluation of the fulfillment of tax obligations at the Hotel X Tax Year 2012. This research was conducted at Hotel X is located in Kerobokan area. Data collected through non-participant observation. The data analysis technique used is a comparative descriptive technique by comparing the results of the calculation of corporate income tax and withholding tax Tax Year 2012 according to calculations by the company with tax laws. The results showed that the Hotel X made ??a mistake in calculating the corporate income tax payable while cutting, depositing, and reporting withholding taxes are in compliance with tax laws.
Keywords: tax review, corporate tax, withholding tax, tax liability